Ultrahigh-strength rare earth magnesium alloy deformed material and preparation method thereof
By adding Nd and Ag elements to Mg-Gd-Y-Zn-Zr alloys and adopting a specific process flow, the problem of insufficient comprehensive mechanical properties of existing ultra-high strength rare earth magnesium alloys is solved, and the deformation of magnesium alloys is realized Ultra-high strength and excellent comprehensive mechanical properties.
Patent Information
- Application Number
- CN202411535100.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The comprehensive mechanical properties of the existing ultra-high strength rare earth magnesium alloys are insufficient, there are too many alloying elements and complex heat treatment processes, which cannot meet the demand for ultra-high strength magnesium alloys in high-tech fields.
By adding Nd and Ag elements to the Mg-Gd-Y-Zn-Zr alloy, the ratio of each metal element is adjusted, and the process flow of smelting, casting, homogenization treatment, variable speed isothermal extrusion and aging treatment is adopted. Prepare ultra-high strength rare earth magnesium alloy deformation material.
The ultra-high strength of the magnesium alloy deformation material was achieved, with a yield strength of 449MPa-454MPa, a tensile strength of 493MPa-502MPa, and an elongation of 9.4%-10.1%, showing excellent comprehensive mechanical properties.
Smart Images

Figure CN119392071A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth magnesium alloy materials, and in particular relates to an ultra-high strength rare earth magnesium alloy deformed material and a preparation method thereof. Background Art
[0002] As the lightest metal structural material in practical application so far, magnesium alloy has the advantages of low density, high specific strength, shock absorption, noise reduction, etc. In recent years, with the increasing awareness of environmental protection and energy conservation in society, lightweighting has become an inevitable trend in the development of various industries. In this era, magnesium alloy has received more and more attention as an alternative material, and plays an increasingly important role in lightweighting and energy conservation and emission reduction.
[0003] Among the existing ultra-high strength rare earth magnesium alloys, for example, Chinese patent publication number CN116804249A discloses a high-strength and toughness deformable rare earth magnesium alloy and a preparation method thereof. The rare earth magnesium alloy includes the following chemical components by mass percentage: Gd: 9-12wt%; Y: 1-3wt%; Zn: 0.5-1.5wt%; Mn: 0.5-0.8wt%; Fe≤0.003wt%; Cu≤0.002wt%; Si≤0.005wt%; Ni≤0.0012wt%; the rest is Mg and inevitable impurities. After secondary solid solution, extrusion deformation, and subsequent heat treatment, the yield strength is 402MPa, the tensile strength is 445MPa, and the elongation is 11%. However, the alloying elements are too many, the heat treatment process is complicated, and the comprehensive mechanical properties cannot meet the demand for ultra-high strength and toughness magnesium alloys in the high technology field. Summary of the invention
[0004] In order to solve the current technical problem of low comprehensive mechanical properties of magnesium alloy materials, the present invention provides an ultra-high strength rare earth magnesium alloy deformed material. By adding Nd and Ag elements and adjusting the ratio of each metal element in the alloy, the yield strength of the magnesium alloy deformed material is 449MPa-454MPa, the tensile strength is 493MPa-502MPa, and the elongation is 9.4%-10.1%, showing excellent comprehensive mechanical properties.
[0005] The technical solution of the present invention is as follows:
[0006] The invention provides an ultra-high strength rare earth magnesium alloy deformation material, which is prepared from the following raw materials in mass fraction: Gd: 7%-8.5%, Y: 2.5%-3.5%, Zn: 1.5%-2.5%, Zr: 0.3%-0.5%, Nd: 0.6-1%, Ag: 1.2%-2%, and the remainder is M.
[0007] The present invention also provides a method for preparing the ultra-high strength rare earth magnesium alloy deformed material, comprising the following steps:
[0008] (1) Melting and casting: weighing the raw materials according to the above mass fractions, melting and casting to obtain magnesium alloy ingots;
[0009] (2) Homogenization treatment: The magnesium alloy ingot is placed at 500-520°C for 18-22 hours, then air-cooled and peeled;
[0010] (3) Variable speed isothermal extrusion treatment: preheating the magnesium alloy billet after homogenization treatment to 440-450°C, preheating the mold to 390-410°C, maintaining the temperature of the magnesium alloy billet above 400°C during the extrusion process, and extruding to obtain a rod;
[0011] (4) Aging treatment: The rod is placed at 190-210°C for 40-50 hours, then taken out for air cooling to obtain an ultra-high strength rare earth magnesium alloy deformed material.
[0012] In one embodiment of the present invention, it is also preferred that the raw materials used in step (1) are Mg ingots, Mg-30Gd master alloys, Mg-30Nd master alloys, Mg-30Y master alloys, Mg-30Zr master alloys, Zn ingots and Ag ingots.
[0013] In one embodiment of the present invention, it is also preferred that the smelting and casting described in step (1) includes first placing the Mg ingot into the furnace for heating and melting, and passing protective gas, and when the furnace temperature rises to 710-750°C, adding Mg-30Gd intermediate alloy, Mg-30Y intermediate alloy and Zn ingot in sequence, and setting the furnace temperature to 740-750°C after keeping warm for 10 minutes, and continuing to keep warm for 15 minutes, and then adding Mg-30Zr intermediate alloy, Mg-30Nd intermediate alloy and Ag ingot in sequence, and continuing to keep warm for 15 minutes for refining, and continuing to stir to obtain alloy liquid, and casting the alloy liquid to obtain magnesium alloy ingot.
[0014] In one embodiment of the present invention, it is also preferred that when the extrusion treatment in step (3) includes extrusion processing, the extrusion ratio is 10-20.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The invention discloses an ultra-high strength rare earth magnesium alloy deformed material. Nd and Ag elements are added to a Mg-Gd-Y-Zn-Zr alloy. The solute atomic clusters formed by Ag and Nd promote dynamic recrystallization, and the co-segregation of Ag and Nd at the recrystallization grain boundary inhibits the growth of recrystallization grains, and finally forms an ultra-fine grain structure, thereby achieving ultra-high strength. Meanwhile, the proportion of each metal element in the Mg-Gd-Y-Zn-Zr alloy is adjusted. The magnesium alloy deformed material exhibits excellent comprehensive mechanical properties, with a yield strength of 449MPa-454MPa, a tensile strength of 493MPa-502MPa, and an elongation of 9.4%-10.1%.
[0017] 1) The maximum solid solubility of Ag and Nd in Mg is 15.5wt% and 3.6wt%, respectively, but their solid solubility decreases sharply with decreasing temperature, so they both show a strong tendency to desolvate. In the early stage of extrusion, dislocations proliferate in large quantities, providing diffusion channels for Ag and Nd desolvation and promoting the formation of solute atomic clusters of Ag and Nd. The atomic clusters can provide nucleation sites for the nucleation of dynamic recrystallization during extrusion, thereby promoting dynamic recrystallization. In addition, Ag and Nd cause opposite lattice distortions in the matrix, and are easy to co-segregate at crystal defects such as dislocations, causing a strong pinning effect on dislocation movement, seriously hindering dislocation rearrangement, thereby forming a large number of dislocation entanglements, which can also serve as nucleation sites for dynamic recrystallization. Ag and Nd also tend to co-segregate at recrystallization grain boundaries, reduce grain boundary interface energy, hinder grain boundary migration, and thus inhibit the growth of recrystallized grains. Under the dual effects of Ag and Nd promoting recrystallization and inhibiting recrystallization growth, ultrafine grain structure is finally formed.
[0018] 2) Ag segregation at the interface between β′ phase and Mg matrix, and Nd changes the aging precipitation kinetics of Gd and Y, thereby increasing the number density of β′ phase and significantly improving the aging hardening response. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The room temperature stress-strain curve of the ultra-high strength rare earth magnesium alloy deformed material of Example 1 of the present invention;
[0020] Figure 2 Room temperature stress-strain curve of the ultra-high strength rare earth magnesium alloy deformed material of Example 2 of the present invention;
[0021] Figure 3 Room temperature stress-strain curve of the magnesium alloy material of Comparative Example 1 of the present invention;
[0022] Figure 4 Room temperature stress-strain curve of the magnesium alloy material of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0024] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0025] An ultra-high strength rare earth magnesium alloy deformed material according to an embodiment of the present invention comprises the following steps:
[0026] (1) Raw material selection: The raw materials used for the alloy are Mg ingot, Mg-30Gd master alloy, Mg-30Nd master alloy, Mg-30Y master alloy, Mg-30Zr master alloy, Zn ingot and Ag ingot.
[0027] (2) First, the Mg ingot is placed in a furnace for heating and melting, and a protective gas is passed through. When the furnace temperature rises to 710-750°C, Mg-30Gd master alloy, Mg-30Y master alloy and Zn ingot are added in sequence, and the temperature is kept at 740-750°C for 15 minutes. Then, Mg-30Zr master alloy, Mg-30Nd master alloy and Ag ingot are added in sequence, and the temperature is kept at 740-750°C for 15 minutes. After that, the alloy liquid is cast into a magnesium alloy billet.
[0028] (3) The magnesium alloy ingot is homogenized by keeping the temperature at 500°C-520°C for 18h-22h, followed by air cooling and peeling. The homogenization process is completed.
[0029] (4) During the variable speed isothermal extrusion process, the magnesium alloy ingot after homogenization treatment is preheated to 440℃-450℃, and the mold is preheated to 390-410℃ to ensure that the temperature is maintained above 400℃ during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 10-20.
[0030] (5) After the isothermal extrusion process is completed, an aging treatment is performed, and the process is as follows: the extruded rod is kept at 190-210°C for 30-40 hours, and then taken out for air cooling.
[0031] The profile variable speed isothermal extrusion technology adopted in the present invention adjusts the extrusion speed in real time based on process simulation, forms a near-isothermal forming environment, and obtains profiles that meet the index performance requirements.
[0032] Example 1
[0033] The method for preparing an ultra-high strength rare earth magnesium alloy deformed material according to embodiment 1 of the present invention comprises the following steps:
[0034] (1) In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes: Gd: 7%, Y: 2.5%, Zn: 1.5%, Zr: 0.3%, Nd: 1%, Ag: 2%, and the balance is Mg.
[0035] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:
[0036] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Nd, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Nd, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.
[0037] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0038] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0039] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0040] At room temperature, according to the test requirements of GB-T 228-2002_Metallic Materials Room Temperature Tensile Test Methods, the yield strength of the magnesium alloy deformed material was measured by a tensile mechanical properties testing machine to be 450MPa, the tensile strength was 502MPa, and the elongation was 9.4%. The room temperature stress-strain curve is shown in Figure 1 shown.
[0041] The mechanical property tests of the following Examples 2 to 8 and Comparative Examples 1 to 2 were all conducted in accordance with GB-T228-2002_Metallic Materials Room Temperature Tensile Test Method.
[0042] Example 2
[0043] The ultra-high strength rare earth magnesium alloy deformed material of the present embodiment 2, the preparation method of which includes the following technical solutions:
[0044] (1) In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes: Gd: 8.5%, Y: 3.5%, Zn: 2.5%, Zr: 0.5%, Nd: 0.6%, Ag: 1.2%, and the balance is Mg.
[0045] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:
[0046] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Nd, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Nd, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.
[0047] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0048] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0049] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0050] At room temperature, the yield strength of the magnesium alloy deformed material was measured by a tensile mechanical properties testing machine to be 454MPa, the tensile strength was 493MPa, and the elongation was 10.1%. Figure 2 shown.
[0051] Example 3
[0052] The method for preparing an ultra-high strength rare earth magnesium alloy deformed material according to Embodiment 3 of the present invention comprises the following steps:
[0053] (1) In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes: Gd: 7%, Y: 2.5%, Zn: 1.5%, Zr: 0.3%, Nd: 0.6%, Ag: 1.2%, and the balance is Mg.
[0054] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:
[0055] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Nd, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Nd, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.
[0056] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0057] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0058] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0059] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 452 MPa, the tensile strength was 496 MPa, and the elongation was 9.5%.
[0060] Example 4
[0061] A method for preparing an ultra-high strength rare earth magnesium alloy deformed material according to embodiment 4 of the present invention comprises the following steps:
[0062] (1) In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes: Gd: 7%, Y: 2.5%, Zn: 1.5%, Zr: 0.3%, Nd: 0.8%, Ag: 1.4%, and the balance is Mg.
[0063] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:
[0064] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Nd, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Nd, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.
[0065] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0066] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0067] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0068] At room temperature, the yield strength of the magnesium alloy deformed material was measured by a tensile mechanical properties testing machine to be 451 MPa, the tensile strength was 501 MPa, and the elongation was 9.7%.
[0069] Example 5
[0070] A method for preparing an ultra-high strength rare earth magnesium alloy deformed material according to Embodiment 5 of the present invention comprises the following steps:
[0071] (1) In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes: Gd: 7%, Y: 2.5%, Zn: 1.5%, Zr: 0.3%, Nd: 0.8%, Ag: 1.8%, and the balance is Mg.
[0072] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:
[0073] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Nd, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Nd, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.
[0074] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0075] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0076] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0077] At room temperature, the yield strength of the magnesium alloy deformed material was measured by a tensile mechanical properties testing machine to be 452 MPa, the tensile strength was 498 MPa, and the elongation was 10%.
[0078] Example 6
[0079] The ultra-high strength rare earth magnesium alloy deformed material of this embodiment 6, the preparation method of which includes the following technical solutions:
[0080] (1) In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes: Gd: 8.2%, Y: 2.7%, Zn: 2%, Zr: 0.4%, Nd: 0.6%, Ag: 1.2%, and the balance is Mg.
[0081] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:
[0082] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Nd, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Nd, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.
[0083] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0084] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0085] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0086] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 451 MPa, the tensile strength was 496 MPa, and the elongation was 9.6%.
[0087] Example 7
[0088] The ultra-high strength rare earth magnesium alloy deformed material of this embodiment 7, the preparation method of which includes the following steps:
[0089] (1) In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes: Gd: 8%, Y: 2.8%, Zn: 1.5%, Zr: 0.4%, Nd: 0.7%, Ag: 1.4%, and the balance is Mg.
[0090] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:
[0091] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Nd, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Nd, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.
[0092] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0093] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0094] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0095] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 450 MPa, the tensile strength was 501 MPa, and the elongation was 9.7%.
[0096] Example 8
[0097] The ultra-high strength rare earth magnesium alloy deformed material of this embodiment 8, the preparation method of which includes the following technical solutions:
[0098] (1) In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes: Gd: 7%, Y: 3.5%, Zn: 1.5%, Zr: 0.5%, Nd: 0.6%, Ag: 1.5%, and the balance is Mg.
[0099] (2) The method for preparing the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes the following steps:
[0100] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, Mg-30Nd, and pure Ag. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then put Mg-30Zr, Mg-30Nd, and pure Ag alloying elements, and continue to keep warm for 15min. Then, the refining and stirring are carried out, and the refining agent is 1.2% of the total weight of the ingredients, that is, 0.06kg. A small ingot is taken out from the melt to measure the direct reading spectrum. If the composition meets the standard, the melt is left to stand for 45 minutes before casting. If the composition does not meet the standard, the material is supplemented until the final direct reading composition is close to the nominal composition.
[0101] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0102] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0103] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0104] At room temperature, the yield strength of the deformed magnesium alloy material was measured by a tensile mechanical properties testing machine to be 449 MPa, the tensile strength was 498 MPa, and the elongation was 9.7%.
[0105] Comparative Example 1
[0106] The preparation method of the magnesium alloy material of Comparative Example 1 comprises the following steps:
[0107] 1. In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes:
[0108] Gd: 7%, Y: 3.5%, Zn: 1.5%, Zr: 0.5%, and the balance is Mg.
[0109] 2. The preparation method of the magnesium alloy deformed material of this comparative example includes the following steps:
[0110] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, and Mg-30Zr. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then add Mg-30Zr alloying elements, and continue to keep warm for 15min. Then refine and stir, and the refining agent takes 1.2% of the total batch weight, that is, 0.06kg. Take a small ingot from the melt and measure the direct reading spectrum. If the composition meets the standard, let the melt stand for 45 minutes before casting. If the composition does not meet the standard, add material until the final direct reading composition is close to the nominal composition.
[0111] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0112] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0113] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0114] At room temperature, the yield strength of the magnesium alloy deformed material was measured by a tensile mechanical properties testing machine to be 344MPa, the tensile strength was 418MPa, and the elongation was 9.6%. Figure 3 shown.
[0115] Comparative Example 2
[0116] The preparation method of the magnesium alloy material of Comparative Example 2 comprises the following steps:
[0117] 1. In terms of mass percentage, the element composition of the ultra-high strength rare earth magnesium alloy deformed material of this embodiment includes:
[0118] Gd: 7%, Y: 3.5%, Zn: 1.5%, Zr: 0.5%, Nd: 0.6%, and the balance is Mg.
[0119] 2. The preparation method of the magnesium alloy deformed material of this comparative example includes the following steps:
[0120] The total weight of each batch is 5kg. When batching, the burnout ratio is adjusted according to the type and content range of the alloying elements. The raw materials used are: pure Mg, Mg-30Gd, Mg-30Y, pure Zn, Mg-30Zr, and Mg-30Nd. Bake the batch and mold before smelting. Set the initial furnace temperature to 710℃, put pure Mg into the furnace and heat it up with the furnace, and pass the protective gas (N2+SF6). When the furnace temperature rises to 710℃, pure Mg begins to melt after about 10min-15min, and the furnace temperature drops to 670℃. When the melt temperature rises to 750℃ again, add Mg-30Gd, Mg-30Y, and pure Zn. After keeping warm for 10min, set the furnace temperature to 750℃, continue to keep warm for 15min, then add Mg-30Zr alloying elements, and continue to keep warm for 15min. Then refine and stir, and the refining agent takes 1.2% of the total batch weight, that is, 0.06kg. Take a small ingot from the melt and measure the direct reading spectrum. If the composition meets the standard, let the melt stand for 45 minutes before casting. If the composition does not meet the standard, add material until the final direct reading composition is close to the nominal composition.
[0121] The magnesium alloy ingot was placed in a muffle furnace at 500°C for 20 hours, followed by air cooling, peeling, and homogenization.
[0122] The magnesium alloy billet after homogenization is subjected to variable speed isothermal extrusion: the alloy billet is preheated to 450°C, the mold is preheated to 400°C, and the temperature is kept at about 400°C during the extrusion process. During the extrusion process, the extrusion ratio is controlled at 17.
[0123] The extruded rod after isothermal extrusion was kept at 200°C for 48 hours and then taken out for air cooling.
[0124] At room temperature, the yield strength of the magnesium alloy deformed material was measured by a tensile mechanical properties testing machine to be 350MPa, the tensile strength was 434MPa, and the elongation was 11.4%. Figure 4 shown.
[0125] The component contents of Examples 1 to 8 are all within the scope of the component contents of the present invention, wherein, Comparative Example 1 does not add Ag and Nd elements, and Comparative Example 2 does not add Ag elements, and the others are the same as Example 8. As shown in Table 1, it can be seen from the room temperature tensile mechanical property test results that the comprehensive mechanical properties of Examples 1 to 8 are significantly higher than those of Comparative Examples 1 to 2. In the field of magnesium alloy materials, it is difficult to increase the absolute mechanical strength after reaching a limit value, especially the yield strength and tensile strength are increased simultaneously. The present invention adds Nd and Ag elements to the Mg-Gd-Y-Zn-Zr alloy, and promotes dynamic recrystallization through the solute atomic clusters formed by Ag and Nd, and the co-segregation of Ag and Nd at the recrystallization grain boundaries inhibits the growth of recrystallized grains, and finally forms an ultrafine grain structure, thereby achieving ultra-high strength, and at the same time adjusting the ratio of each metal element in the Mg-Gd-Y-Zn-Zr alloy. Compared with comparative examples 1 and 2, the yield strength is increased by nearly 100 MPa, the tensile strength is increased by nearly 70 MPa, and the elongation is still maintained at 9.4%-10.1%. Therefore, the magnesium alloy deformed material of the present invention exhibits excellent comprehensive mechanical properties, with a yield strength of 449 MPa-454 MPa, a tensile strength of 493 MPa-502 MPa, and an elongation of 9.4%-10.1%. Therefore, in the ultra-high strength rare earth magnesium alloy deformation of the present invention, the addition of Nd and Ag elements to the Mg-Gd-Y-Zn-Zr series rare earth deformed magnesium alloy can significantly improve the comprehensive mechanical properties of the material, and the absolute strength is significantly improved.
[0126] Table 1 Room temperature mechanical properties of the embodiments and comparative examples
[0127] Serial number Tensile strength(MPa) Yield strength (MPa) Elongation(%) Example 1 502 450 9.4 Example 2 493 454 10.1 Example 3 496 452 9.5 Example 4 501 451 9.7 Example 5 498 452 10 Example 6 496 451 9.6 Example 7 501 450 9.7 Example 8 498 449 9.7 Comparative Example 1 418 344 9.6 Comparative Example 2 434 350 11.4
[0128] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An ultra-high strength rare earth magnesium alloy deformed material, characterized in that: Made from the following raw materials by mass fraction: Gd: 7%-8.5%, Y: 2.5%-3.5%, Zn: 1.5%-2.5%, Zr: 0.3%-0.5%, Nd: 0.6-1%, Ag: 1.2%-2%, the balance is Mg.
2. A method for preparing the ultra-high strength rare earth magnesium alloy deformed material according to claim 1, characterized in that: The following steps are involved: (1) Melting and casting: weighing raw materials according to the mass fraction of claim 1, melting and casting to obtain a magnesium alloy ingot; (2) Homogenization treatment: The magnesium alloy ingot is placed at 500-520°C for 18-22 hours, then air-cooled and peeled; (3) Variable speed isothermal extrusion treatment: preheating the magnesium alloy billet after homogenization treatment to 440-450°C, preheating the mold to 390-410°C, maintaining the temperature of the magnesium alloy billet above 400°C during the extrusion process, and extruding to obtain a rod; (4) Aging treatment: The rod is placed at 190-210°C for 40-50 hours, then taken out for air cooling to obtain an ultra-high strength rare earth magnesium alloy deformed material.
3. The method for preparing the ultra-high strength rare earth magnesium alloy deformed material according to claim 2, characterized in that: The raw materials used in step (1) are Mg ingots, Mg-30Gd master alloys, Mg-30Nd master alloys, Mg-30Y master alloys, Mg-30Zr master alloys, Zn ingots and Ag ingots.
4. The method for preparing the ultra-high strength rare earth magnesium alloy deformed material according to claim 3, characterized in that: The smelting and casting described in step (1) include first placing the Mg ingot into a furnace to heat and melt it, and passing a protective gas, and when the furnace temperature rises to 710-750°C, adding Mg-30Gd master alloy, Mg-30Y master alloy and Zn ingot in sequence, and setting the furnace temperature to 740-750°C after keeping warm for 10 minutes, and continuing to keep warm for 15 minutes, and then adding Mg-30Zr master alloy, Mg-30Nd master alloy and Ag ingot in sequence, and continuing to keep warm for 15 minutes for refining, and continuing to stir to obtain alloy liquid, and casting the alloy liquid to obtain a magnesium alloy ingot.
5. The method for preparing the ultra-high strength rare earth magnesium alloy deformed material according to claim 2, characterized in that: The extrusion treatment in step (3) includes an extrusion process with an extrusion ratio of 10-20.
Citation Information
Patent Citations
High-toughness deformed rare earth magnesium alloy and preparation method thereof
CN116804249A
Magnetic head cleaning cassette
GB2282002A